Serratia Fonticola microbe presented as a community-acquired urinary tract infection (UTI): a case report (Journal of Ideas in Health, 2020)
Background: The case we are presenting is about one of the rare pathogens, Serratia Fonticola (SF) that may cause urinary tract infection. Case Presentation: A 58 years-old female presented with dysuria, suprapubic pain, frequency of micturition, and change in urine color. The patient was afebrile on physical examination; however, the urine culture was positive to SF as the sole isolate. The patient received levofloxacin tables (750 mg) once a day for 5 days along with supportive instructions to improve hygiene. On follow-up, she was free of symptoms and the repeated urine culture was negative.Conclusion: This case can be considered globally the third that diagnosed in the urine culture of the asymptomatic patient. References• Geerlings SE. Clinical presentations and epidemiology of urinary tract infections. Microbiol. Spectr. 4, 2016. https://doi.org/10.1128/9781555817404.ch2• Flores-Mireles AL, Walker JN, Caparon M, Hultgren SJ. Urinary tract infections: epidemiology, mechanisms of infection and treatment options. Nat Rev Microbiol. 2015 May;13(5):269-84. https://doi.org/10.1038/nrmicro3432• Gavini F, Ferragut C, Izard D, Trinel PA, Leclerc H, Lefebvre B, Mossel DA. Serratia fonticola, a new species from water. International Journal of Systematic and Evolutionary Microbiology. 1979;29(2):92-101. https://doi.org/10.1099/00207713-29-2-92• Aljorayid A, Viau R, Castellino L, Jump RL. Serratia fonticola, pathogen or bystander? A case series and review of the literature. IDCases. 2016 May 24; 5:6-8. https://doi.org/10.1016/j.idcr.2016.05.003• Müller HE. Isolation of Serratia fonticola from birds. Zentralblatt Bakteriol Mikrobiol Und Hyg - Abt 1 Orig A 1986; 261:212–8. https://doi.org/10.1016/s0176-6724(86)80038-4• Garcia ME, Lanzarot P, Costas E, Lopez Rodas V, Marín M, Blanco JL. Isolation of Serratia fonticola from skin lesions in a Nile Crocodile (Crocodylus niloticus) with an associated septicaemia. Vet J. 2008 May;176(2):254-6. https://doi.org/10.1016/j.tvjl.2007.02.025.• Bollet C, Gainnier M, Sainty JM, Orhesser P, De Micco P. Serratia Fonticola isolated from a leg abscess. J Clin Microbiol 1991; 29:834–5. https://doi.org/10.1128/JCM.29.4.834-835.1991• Farmer JJ 3rd, Davis BR, Hickman-Brenner FW, McWhorter A, Huntley-Carter GP, Asbury MA, Riddle C, Wathen-Grady HG, Elias C, Fanning GR, et al. Biochemical identification of new species and biogroups of Enterobacteriaceae isolated from clinical specimens. J Clin Microbiol. 1985 Jan;21(1):46-76. https://doi.org/10.1128/JCM.21.1.46-76.1985• Stock I, Burak S, Sherwood KJ, Gruger T, Wiedemann B. Natural antimicrobial susceptibilities of strains of 'unusual' Serratia species: S. ficaria, S. fonticola, S. odorifera, S. plymuthica and S. rubidaea. J Antimicrob Chemother. 2003;51(4):865-85. https://doi.org/10.1093/jac/dkg156.• Gorret J, Chevalier J, Gaschet A, Fraisse B, Violas P, Chapuis M, Anne JG. Childhood delayed septic arthritis of the knee caused by Serratia fonticola. Knee 2009; 16 (6):512–4. https://doi.org/10.1016/j.knee.2009.02.008• Hai PD, Hoa LTV, Tot NH, Phuong LL, Quang VV, Thuyet BT, Son PN. First report of biliary tract infection caused by multidrug-resistant Serratia fonticola. New Microbes New Infect. 2020; 36:100692. https://doi.org/10.1016/j.nmni.2020.100692Conclusion: This case can be considered globally the third that diagnosed in the urine culture of the asymptomatic patient.
Keywords: Serratia Fonticola, Urinary Tract Infection, Female, Case Report, Community, Saudi Arabia